Severe Generalized Tetanus in a Child with a History of a Nail Puncture Wound and Chronic Dental Infection: A Case Report - ST. Miftahayatun (Riviera Publishing, 2026)
Tetanus is an acute infectious disease caused by the toxin of Clostridium tetani, which affects the nervous system and results in progressive muscle rigidity and spasms. Although immunisation is available and effective, tetanus cases continue to occur in developing countries, often associated with inadequately treated open wounds and incomplete immunisation. This case report describes a rare presentation of severe generalised tetanus in a 13-year-old boy with suspected multiple portals of entry. The patient presented with progressive stiffness and pain in the abdomen, back, neck, and jaw. He had a history of a nail puncture wound one month prior to admission, without having received post-exposure tetanus immunisation. Oral examination revealed chronic apical periodontitis of tooth 16 and a habit of self-inflicted needle trauma to the teeth. The patient was admitted to the intensive care unit under isolation and received antitetanus serum, combination antibiotic therapy, and prolonged sedation. This case highlights the importance of clinical vigilance for tetanus, the critical role of immunisation, and the need for adequate wound management and treatment of chronic infections to prevent severe complications. The possibility of more than one portal of entry — including chronic oral cavity infections — should be considered in the clinical evaluation of tetanus patients, particularly in paediatric populations with incomplete immunisation status.